Role of the brain-derived neurotrophic factor at glutamatergic synapses - Carvalho, A. L. (2008)
The neurotrophin brain-derived neurotrophic factor (BDNF) plays an important role in the activity-dependent regulation of synaptic structure and function, particularly of the glutamatergic synapses. BDNF may be released in the mature form, which activates preferentially TrkB receptors, or as proBDNF, which is coupled to the stimulation of the p75(NTR). In the mature form BDNF induces rapid effects on glutamate release, and may induce short- and long-term effects on the postsynaptic response to the neurotransmitter. BDNF may affect glutamate receptor activity by inducing the phosphorylation of the receptor subunits, which may also affect the interaction with intracellular proteins and, consequently, their recycling and localization to defined postsynaptic sites. Stimulation of the local protein synthesis and transcription activity account for the delayed effects of BDNF on glutamatergic synaptic strength. Several evidences show impaired synaptic plasticity of glutamatergic synapses in diseases where compromised BDNF function has been observed, such as Huntington's disease, depression, anxiety, and the BDNF polymorphism Val66Met, suggesting that upregulating BDNF-activated pathways may be therapeutically relevant. This review focuses on recent advances in the understanding of the regulation of the glutamatergic synapse by BDNF, and its implications in synaptic plasticity